Preparedness for Fire Emergency in the Nutrition Laboratory at University X in Semarang: as a Safety Education for University Students - Laura Marulia S.; Nabila Gustin Eka N.R.; Nisa Trisna N.; Hany Risna A.; Bellinda Annisa P.; Daniel Bendon Tangdi (Universitas Negeri Semarang, 2023)
The Occupational Safety and Health Administration (OSHA) indicates that academic laboratories are 11 times more dangerous than the industrial sectors. The nutrition laboratory is a place that has a high potential to cause fire because there are cooking activities, where these activities are very risky because they deal directly with fire and gas cylinders there. If the gas cylinder has a leak, it can cause a fire risk. This study aims to look at the preparedness of fire disaster management in the Nutrition Laboratory at University X in Semarang city. The research design used in this research was a descriptive qualitative. There were 3 informants, namely the person in charge of the nutrition laboratory and 2 students of the Nutrition Study Program. Data collection techniques used in this research was in-depth interviews. The results showed that the nutrition laboratory at University X in Semarang city already had management related to fire prevention such as the availability of fire extinguishers, evacuation routes, and assembly points. It is recommended that related parties complete active and passive protection systems, improve fire prevention teams, train and socialize, and conduct regular testing of active protection facilities in the Nutrition Laboratory.